A Model for Understanding Mandatory System Implementation: A Literature Review - Monica Agustami Kristy; Paulus Insap Santosa; Ridi Ferdiana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The system implementation within the company or organization is accompanied by the redesign of business processes and changes in organizational structure that are carried out to align system implementation with business strategies. In a mandatory environment,, the decision to adopt technology is determined by the management so that in the end employees will use the technology. However, there is a possibility that the employee may engage in destructive behavior so that failing to implement innovations or technology. Many studies have developed models that can be used to measure the success of mandatory system implementation and identified the factors that influence that success. The purpose of this literature review is to provide a comprehensive summary of research related to the success model of mandatory system implementation, provide insight into the critical success factors of mandatory system implementation, and identify research limitations in the literature to provide possible future. The research selected in this literature review is research from 2016 to 2021.